Farhang-i Jāmiʿ al-lughāt : Farhang-i manẓūm - Ḥijāzī, Niyāzī, (Miras Maktoob, ISBN: 9789004365452., 2019)
The history of Arabic and Persian lexicography is long and extremely varied. But no matter what dictionary one is looking at, it is always organized in a certain way and always has a certain level of detail. Thus, some of the early Arabic dictionaries centered around one or more particular themes, such as insects or weapons. Other dictionaries, and this the majority, brought together any word material, irrespective of subject or theme. Besides, some dictionaries offered a lot of material in explanation of some term while others offered less. And then, some dictionaries contained explanations or samples in verse rather than prose. Examples of the latter in Persian are Ibrāhīm Qawām Fārūqī's Sharafnāma-yi Manyarī (877/1472) and the Lughat-i Furs by the poet Abū Naṣr Asadī Ṭūsī (d. 465/1072). The dictionary edited here for the very first time stands in this same tradition. Composed in the 10th/16th century, in contains 1600 entries in Persian and Arabic.